The economic development incentive mechanism for the existing energy-saving building structure in the perspective of game analysis. (4th July 2018) - Li, Yin; Liang, Mei
Abstract: Building energy conservation in north heating areas is an important component of energy saving and emission reduction. Due to the shortcomings of high energy consumption, low efficiency and poor comfort, it is urgent to reform the energy conservation of the existing buildings in the north. To perfect the energy reconstruction of the existing buildings and promote the rapid and stable development of building energy conservation, this study first confirmed and analyzed the influence factors for building energy-saving market, established models for economic incentive subjects in the perspective of game analysis and made game strategy analyses on the central government and regional government, government and social subject. Then, the economic incentive mechanism for energy saving of the existing buildings was investigated in the perspective of game analysis. Market development and governmental promotion were both involved in building energy-saving reconstruction. The government is advised to promote the smooth proceeding of building energy saving by maintaining subject investment balance, lowering the threshold of energy-saving reconstruction of the existing buildings and giving credit for the determination of relevant enterprises to building energy saving.